2004
DOI: 10.1111/j.1365-3040.2003.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rising CO2 on emissions of volatile organic compounds: isoprene emission from Phragmites australis growing at elevated CO2 in a natural carbon dioxide spring

Abstract: Isoprene basal emission (the emission of isoprene from leaves exposed to a light intensity of 1000 m m m m mol m ----2 s ----1 and maintained at a temperature of 30 ∞ ∞ ∞ ∞ C) was measured in Phragmites australis plants growing under elevated CO 2 in the Bossoleto CO 2 spring at Rapolano Terme, Italy, and under ambient CO 2 at a nearby control site. Gas exchange and biochemical measurements were concurrently taken. Isoprene emission was lower in the plants growing at elevated CO 2 than in those growing at ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 28 publications
(39 reference statements)
6
87
0
Order By: Relevance
“…Isoprene is formed predominantly from photosynthetic carbon fixation (Sharkey & Yeh 2001) and it was expected that the two processes be simultaneously stimulated by increasing availability of CO2. However, exposure to or growth at elevated CO2 often reduce isoprenoid emission by vegetation (Loreto & Sharkey 1990, Loreto et al 2001a, Scholefield et al 2004, Rosen stiel et al 2003, with few exceptions (e.g., Sharkey et al 1991, Rapparini et al 2001. This uncoupling between the two processes may be due to an inhibition of isoprene syn thase activity under elevated CO2 (Schole field et al 2004) or to a reduction of the availability of isoprene synthase substrate (predominantly dimethylallyl diphosphate (DMADP), Rosenstiel et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoprene is formed predominantly from photosynthetic carbon fixation (Sharkey & Yeh 2001) and it was expected that the two processes be simultaneously stimulated by increasing availability of CO2. However, exposure to or growth at elevated CO2 often reduce isoprenoid emission by vegetation (Loreto & Sharkey 1990, Loreto et al 2001a, Scholefield et al 2004, Rosen stiel et al 2003, with few exceptions (e.g., Sharkey et al 1991, Rapparini et al 2001. This uncoupling between the two processes may be due to an inhibition of isoprene syn thase activity under elevated CO2 (Schole field et al 2004) or to a reduction of the availability of isoprene synthase substrate (predominantly dimethylallyl diphosphate (DMADP), Rosenstiel et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A portion of the leaf was clamped in the cuvette of a portable Li-Cor 6400 (LiCor, Lincoln, NE, USA) gas exchange sys tem as described by Scholefield et al (2004). This system allows very fast changes of CO2 concentration (380 ppm or 900 ppm) and source ( 12 CO2 or 13 CO2) or light intensity while controlling all other environmental pa rameters.…”
Section: Gas-exchange Measurementsmentioning
confidence: 99%
“…However, no evidence of changes in total carotenoids and in xanthophylls deepoxidation status Scholefield et al, 2004) were previously found upon fosmidomycin feeding for short periods (up to 1 h). Similar results were found in these experiments, being the deepoxidation status of xanthophylls independent of fosmidomycin, while the total amount of xanthophylls was slightly but not significantly reduced following fosmidomycin feeding (data not shown).…”
mentioning
confidence: 89%
“…The fundamental logic of such models is that changes in NPP will produce more or less biomass capable of emitting isoprene, and changes in climate (principally temperature) will stimulate or inhibit emissions per unit of biomass. These models tend to ignore the discovery that there are direct effects of changes in the atmospheric CO 2 concentration on isoprene emission that tend to work in the opposite direction to that of stimulated NPP (Sanadze 1964;Monson & Fall 1989;Rosenstiel et al 2003;Centritto et al 2004;Rapparini et al 2004;Scholefield et al 2004;Possell et al 2005; figure 1). Progress has been made in the past few years on the biochemical mechanisms underlying this direct response (Rosenstiel et al 2003(Rosenstiel et al , 2004, and it is now possible to propose strategies for incorporating these effects into surface emission models.…”
Section: Introductionmentioning
confidence: 99%